Analisis Perbandingan Usahatani Kentang Varietas Granola dan Varietas Cipanas di Desa Sungai Lintang Kecamatan Kayu Aro Barat Kabupaten Kerinci - Cindi Fatikasari; Mahmud; Herda Gusvita (Jurnal Research Ilmu Pertanian, 2024)
The aims of this study were: (1) To determine the characteristics of potato farmers of the Granola variety and Cipanas variety in Sungai Lintang Village, Kayu Aro Barat District; (2) To find out the difference in potato production, total costs, receipts, income, and profits of the Granola variety and the Cipanas variety in Sungai Lintang Village, Kayu Aro Barat District. The method used in this research is a quantitative descriptive method. Based on the results of the study, it was found that : This research was conducted from 28 August – 28 September 2022 with a total sample of 90 potato farmers of the Granola variety and 45 potato farmers of the Cipanas variety. Based on the results of the study, it was found that: (1) Characteristics of potato farmers in Sungai Lintang Village include: There are 2 age groups with the same frequency, namely between 23-29 and 44-50 years old as many as 23 people (25.55%) for Granola Variety potato farmers, while the most Cipanas Potato Farmers are 37-43 years old as many as 15 people (26.66%). The experience of farming the most potato farmers is between 23-30 years as many as 35 people (38.89%) for the Granola variety, while the potato farmers for the Cipanas variety are 20 people (44.44%). The highest level of educated average was 40 people (44.44%) with high school educated average for Granola variety potato farmers and 21 people (46.66%) with junior high school education for Cipanas variety potato farmers. The largest area of land cultivated by potato farmers with a land area of 0.25 – 0.46 Ha was 74 people (82.22%) potato farmers of the Granola variety and 42 people (93.33%) potato farmers of the Cipanas variety. The highest number of dependents of the potato farming families, between 3-4 for the Granola variety potato farmers, was 66 people (73.33%) and 36 people (80.00%) for the Cipanas variety potato farmers; (2) There are differences in production, total costs, revenues, and profits for potato farming of the Granola variety and the Cipanas variety in Sungai Lintang Village; (2) There are differences in production, total costs, revenues, and profits for potato farming of the Granola variety and the Cipanas variety in Sungai Lintang Village; (3) There is no difference in income for potato farming of the Granola variety and the Cipanas variety in Sungai Lintang Village. Based on the results of the study, the researchers suggest that farmers should focus more on planting the Granola Variety potatoes, because economically the production is higher, and the profits are also greater. while the total costs incurred for the Granola variety were less than the Cipanas variety